Responsive Islamic Education on Women's Politics: Women's Strategy in Political Disputes in the Digital Era - Muslimin; Luluk Maktumah; Siti Kholida; Hosaini; Farhatin Masruroh (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
In recent decades, the role of women in politics has significantly evolved in many countries, including within the context of Muslim societies. Despite progress, women still face complex challenges limiting their political participation. This research employs a literature review method to explore the strategies utilized by women in addressing political disputes in the digital era and how Islamic education can reinforce these strategies. The findings indicate that women employ various tactics, including leveraging social media and online networks, to overcome political barriers. Additionally, this study examines the impact and implications of digital technology usage on women's political participation, highlighting associated potentials and risks. Based on these findings, the research proposes solutions that can be implemented through a more inclusive and gender-sensitive approach to Islamic education. The study aims to contribute to understanding the relationship between Islamic education, women's politics, and the digital age, while strengthening women's active role in political and social life.